A leanderrák kórokozójának, a Pseudomonas savastanoi pv. nerii baktériumfaj izolátumainak azonosítása és összehasonlítása hazánkban - Fodor, Attila; Palkovics, László; Juhász, Áron; Végh, Anita (GEORGIKON FOR AGRICULTURE, 2022)
Oleander (Nerium oleander L.) is a popular woody ornamental plant. Unfortunately, a plant pathogenic bacterium, Pseudomonas savastanoi pv. nerii causes serious disease with neoplastic lesions in all parts of the plant. This disease is called oleander cancer. Between 2020 and 2021 we collected many infected plant parts nationwide and examined the pathogen by classical methods - hypersensitivity reaction, Gram-property, biochemical characteristics (API20 NE), pathogenicity test, LOPAT test.
Keywords: Nerium oleander; Pseudomonas savastanoi pv. nerii; oleander cancer